Enhanced expression of CD39 and CD73 on T cells in the regulation of anti-tumor immune responses. (1st January 2020) - Shevchenko, Ivan; Mathes, Andreas; Groth, Christopher; Karakhanova, Svetlana; Müller, Verena; Utikal, Jochen; Werner, Jens; Bazhin, Alexandr V.; Umansky, Viktor
ABSTRACT: Synthesis of extracellular adenosine by the ectonucleotidases CD39 and CD73 represents an important pathway of immune suppression in the tumor microenvironment. Using two mouse models ( RET transgenic melanoma and Panc02 orthotopic pancreatic adenocarcinoma), we identified an elevated frequency of ectonucleotidase-expressing T cells in tumors and spleens. Importantly, these ectonucleotidase-positive T cells also showed a pronounced expression of PD-1. Conversely, the PD-1 + T cell subsets in tumors contained substantially larger proportions of ectonucleotidase-expressing cells compared to their counterparts lacking PD-1 expression. Our in vitro experiments showed that the activation of normal T cells resulted in an increase in the CD39 expression. CD39 + and CD73 + T cells displayed effector or memory phenotypes and produced IFN-γ, thereby linking ectonucleotidase expression to T cell effector functions. An accumulation of conventional and regulatory T cells expressing CD39 and/or CD73 was also detected in the peripheral blood of patients with melanoma and pancreatic cancer. Moreover, we demonstrated a significant association between low frequencies of circulating CD73 + CD8 + T cells and CD73 + CD4 + regulatory T cells and better overall survival of melanoma patients. Tumor-derived soluble factors (in particular, TGF-β) significantly enhanced the frequencies of ectonucleotidase-expressing cells in mice. Our findings suggest that the upregulation of ectonucleotidase expression in T cells promotes extracellular adenosine accumulation and represents an important mechanism of homeostatic immune auto-regulation, which could be hijacked by tumors to evade anti-cancer immunity. Targeting CD39 and CD73 can open new avenues for cancer immunotherapy.